ANALISIS KECUKUPAN SARANA PRASARANA, DISIPLIN KERJA, PENGAWASAN PEKERJAAN DAN KOMPETENSI KARYAWAN PADA PERUSAHAAN PT. PEMBANGKITAN JAWA-BALI UNIT BISNIS JASA OPERATION & MAINTENANCE PLTU REMBANG - jurnalmap map; Rusminto ÔÇì; Cathrine Sri Hartati; Gurendro Putro (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This study aims to find out, analyze and discuss events that occurred in UBJ's PLTU Rembang Operation & Maintanance (O & M) Business Unit which had an impact on casualties, asset damage, production / financial loss, influence of the use of UBJ O & M Rembang PLTU. This type of research is descriptive with qualitative methods. This research was conducted at PT. Pembangkitan Jawa-Bali Business Unit for Operation and Maintenance Services (O & M) of Rembang PLTU. The results of the research related to the adequacy of infrastructure / SOPs are good, but there are still those who oppose management related to employee discipline in the application of SOPs, factors of work supervision, and human resources are still lacking. Keywords: facilities, work discipline, supervision of work, competence